Temperature Response in Hardened Concrete Subjected to Tropical Rainforest Environment - Egba, E. I.; Ismail, M.; Bakhary, N. (Engineering, Technology & Applied Science Research, 2017)
The objective of this paper is to characterize concrete micro-environment temperature response to the natural climate of the tropical rainforest. The peculiar warmth, high humidity, and low pressure nature of the tropical rainforest necessitated the present study. Temperature probes were inserted into concrete specimens subjected to the sheltered and unsheltered environment to measure the micro-environment temperature of the concrete, and study the hysteresis characteristics in relation to the climate temperature. Some mathematical relationships for forecasting the internal temperature of concrete in the tropical rainforest environment were proposed and tested. The proposed relationships were found reliable. It was observed that the micro-environment temperature was lower at the crest, and higher at the trough than the climate environment temperature with a temperature difference of 1-3 oC. Also, temperature response in concrete for the unsheltered micro-environment was 1.85 times faster than the response in the sheltered micro-environment. The findings of the study may be used to assist the durability assessment of concrete.